2019
DOI: 10.1017/s1049023x19004333
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Characteristics of Security Incidents Involving Aid Workers in Health Care Settings: A 20-Year Review

Abstract: Introduction:In recent years, several high-profile attacks on hospitals providing medical aid in conflict settings have raised international concern. The International Humanitarian Law prohibits the deliberate targeting of health care settings. Violation of this law is considered a war crime and impacts both those delivering and receiving medical aid.Problem:While it has been demonstrated that both aid workers and health care settings are increasingly being targeted, little is known about the trends and charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…[15][16][17] Vaccinators in higher-income countries operate in similar environments but there are important differences in how they have been attacked. A 20-year review by Morokuma et al 18 found that the most common method of attack against aid workers was bombing followed by gun attacks. In our study, however, terrorists who attacked vaccinators were more likely to use firearms than bombs.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Vaccinators in higher-income countries operate in similar environments but there are important differences in how they have been attacked. A 20-year review by Morokuma et al 18 found that the most common method of attack against aid workers was bombing followed by gun attacks. In our study, however, terrorists who attacked vaccinators were more likely to use firearms than bombs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it was recently shown that security threats are a growing occupational hazard for health-care workers, including laboratory staff [5]. This study emphasizes the need for better monitoring of such risks and improving counter-strategies to ensure the safety of staff in dangerous zones [5].…”
Section: Mobile Microbiology: Settings and Challengesmentioning
confidence: 92%
“…Patiriamas smurtas ir agresija darbo metu padidina slaugytojų jaučiamą įtampą, ir tai lemia jų nepasitenkinimą darbu. Nepasitenkinimą darbu rodo darbo produktyvumas ir našumas, priežiūros paslaugų kokybė, darbuotojų kaita, įsipareigojimas organizacijai ir pacientų sauga (Stene et al, 2015;Zhao, et al, 2018;Morokuma, Chiu, 2019).…”
Section: įVadasunclassified